2023
DOI: 10.1186/s41118-023-00197-7
|View full text |Cite
|
Sign up to set email alerts
|

Childcare in Italy among migrants and natives: who uses which type and why?

Abstract: The Italian welfare state is characterised by a preference for income transfers over transfers in kind and the marginal role of policies aimed directly at supporting the family. Despite the growing participation of women in the labour market, the Italian welfare system still assumes the family, with its unbalanced gender division of housework and its intergenerational solidarity, to be the primary provider of protection and support. As a result, in Italy in 2019 only 26.9% of children under 3 years of age were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Given these constraints, scholars have demonstrated that migrant parents tend to adopt several informal solutions, with differences driven by family migration patterns (Wall & José, 2004). Previous research has emphasised the role of family structure in the selection of childcare arrangements, such as children's age, the presence of siblings, a partner and grandparents (in good health, co-resident or living nearby), parents' employment status and local and transnational kinship relations, as certain individuals can represent important sources of childcare (Barglowski et al, 2015;Bilecen & Sienkiewicz, 2015;Grysole, 2018;Mussino & Ortensi, 2023;Ryan, 2011aRyan, , 2011bTrappolini et al, 2021Trappolini et al, , 2023Zanasi et al, 2022).…”
Section: Conceptual Framework and Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Given these constraints, scholars have demonstrated that migrant parents tend to adopt several informal solutions, with differences driven by family migration patterns (Wall & José, 2004). Previous research has emphasised the role of family structure in the selection of childcare arrangements, such as children's age, the presence of siblings, a partner and grandparents (in good health, co-resident or living nearby), parents' employment status and local and transnational kinship relations, as certain individuals can represent important sources of childcare (Barglowski et al, 2015;Bilecen & Sienkiewicz, 2015;Grysole, 2018;Mussino & Ortensi, 2023;Ryan, 2011aRyan, , 2011bTrappolini et al, 2021Trappolini et al, , 2023Zanasi et al, 2022).…”
Section: Conceptual Framework and Empirical Evidencementioning
confidence: 99%
“…Most existing studies on childcare focus on the choices of the overall population, generally considering migrants to be childcare providers rather than potential consumers of such services (Mussino & Ortensi, 2023;Williams & Gavanas, 2016). Of course, childcare becomes much more complex when parents are migrants settling in a new country.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, structural hindrances, including limited accessibility and high costs, affect both native and migrant families' childcare service utilization ( Van Lancker & Pavolini, 2023). Our Thematic Series contributes to the literature on childcare use through three articles that pursue different approaches and focus on different migrant populations and migrant generations in different European migrant receiving countries: Eremenko and Unterreiner (2023)-in this Thematic Series) examined the patterns of ECEC enrolment among parents belonging to recent migrant populations in France who have children under the age of 3 years, while Mussino and Ortensi (2023)-in this Thematic Series) investigated the influence of parental age at arrival on variations in childcare use among migrants in Italy, in comparison to the native population. Previous research has identified a gap in the use of formal childcare services between migrant and native families across European countries, with migrants generally using these services less (Biegel et al, 2021;Schober & Spiess, 2013;Schmitz et al, 2023).…”
Section: Family Policy Dimensions: Parental Leave and Early Childhood...mentioning
confidence: 99%
“…In particular, children of migrant background often change for the worse their traditional eating habits while increasing consumption of processed food often because of economic barriers [13,14]. Given that as of January 1, 2020, Italy was counting 1.3 million children of migrant background aged 0-17, it's clear how the imprinting of nutritional and healthy lifestyle education among this population group is determinant to curb childhood obesity prevalence in future years [15].…”
Section: Introduction Backgroundmentioning
confidence: 99%